The status of insecticide resistance of Anopheles coluzzii on the islands of São Tomé and Príncipe, after 20 years of malaria vector control - Maria Correa; Janete Lopes; Carla A. Sousa; Gustavo Rocha; Robin Oriango; Andreia Cardetas; Joao Viegas; Anthony J. Cornel; Gregory C. Lanzaro; João Pinto (Malaria Journal)
Abstract Background Insecticide-based malaria vector control has been implemented on the islands of São Tomé and Príncipe (STP) for more than 20 years. During this period malaria incidence was significantly reduced to pre-elimination levels. While cases remained low since 2015, these have significantly increased in the last year, challenging the commitment of the country to achieve malaria elimination by 2025. To better understand the reasons for increasing malaria cases, levels and underlying mechanisms of insecticide resistance in the local Anopheles coluzzii populations were characterized. Methods Mosquito larval collections were performed in the rainy and dry seasons, between 2022 and 2024, in two localities of São Tomé and one locality in Príncipe. Susceptibility to permethrin, α-cypermethrin, pirimiphos-methyl and DDT was assessed using WHO bioassays and protocols. Intensity of resistance and reversal by PBO pre-exposure were determined for pyrethroid insecticides. The kdr locus was genotyped by PCR assays in subsamples of the mosquitoes tested. Results Anopheles coluzzii populations were fully susceptible to pirimiphos-methyl, but high levels of resistance to pyrethroids and DDT were detected, particularly in São Tomé rainy season collections. Increasing the pyrethroid and DDT dosages to 5 $$×$$ × and 10 $$×$$ × did not restore full susceptibility in all populations. Pre-exposure to PBO resulted into partial reversal of the resistance phenotype suggesting the presence of cytochrome P450 oxidases-mediated metabolic resistance. The L1014F knockdown resistance mutation was present in An. coluzzii on both islands but at much higher frequency in São Tomé where it was associated with the resistant phenotype. Conclusions Future vector control interventions should consider the use of non-pyrethroid insecticides or combination with synergists to overcome the high levels of pyrethroid resistance. Alternative control methods not dependent on the use of insecticides should be additionally implemented to achieve malaria elimination in STP.